Grammar Errors in Animated Youtube Channel Santoon TV with Content Titled "Respect Teachers, Love Friends" - Adrianie, Melisya; Wicaksono, Roid; Simanjuntak, Nensy Megawati (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
The aim of this research was to find out and identify language errors in the Santoon TV YouTube channel animation entitled "Respect teachers, love friends" both in terms of writing and visuals. This further directs research into decoding words that are poorly slurred in the animation to make the research object a learning object. Often seen by people from various groups from children to adults. The author uses a qualitative descriptive research approach which aims to analyze in depth the meaning and message contained in the animation. with the decoding of words created in this journal, we can better understand the value of better pronunciation of words from the animation, as well as deciphering the values ​​that we want to convey to the audience, especially children. The data used in this research is poor word decoding in a video. The data collection techniques used in this research are screen capture, observation and listening. The analysis technique used in this journal is Qualitative Descriptive. The results of this research showed that there were various language errors and misunderstandings in the language grammar charts which were spoken rudely and impolitely on Santoon TV's YouTube channel entitled "Respect teachers, love friends".